DESIGN, DEVELOPMENT AND IN VITRO EVALUATION OF CAFFEINE LOADED NATURAL GUM MATRIX TABLET - Jain, Nidhi; Kumar, Divya; Gulati, Neha; Nagaich, Upendra (INDONESIAN JOURNAL OF PHARMACY, 2013)
The present research work was carried out to develop sustained release tablets of caffeine using natural matrix former (tragacanth) and different filling polymers like hydroxyl propyl methyl cellulose (HPMC K15M) and ethyl cellulose (EC). Caffeine was used as model drug. The polymers and tragacanth gum were incorporated in varying ratios into a matrix system using wet granulation technique. All the lubricated formulations were compressed into tablets and evaluated for various physicochemical properties such as thickness, hardness, friability, weight variation, drug content and in vitro drug release studies. From the investigation it was observed that increase in the amount of gum tragacanth (from F1 to F5) led to reduced friability, increased hardness and retarded drug release. Different filling polymers also sustained the drug release. The in vitro drug release data were tted in various release kinetics models to understand th mechanism of drug release. All solid matrix formulations were found to follow Higuchi kinetics, indicating the diffusional release of drug from the matrix type system. The Formulation F5 containing highest amount of gum tragacanth have shown promising results. The findings of the current investigation clearly indicate the potential of tragacanth gum to be used as release retardant and natural matrix material in sustained release formulations. Key words: Sustained release, Matrix tablets, Tragacanth, Caffeine.